Review of Epidemiology and Antifungal Susceptibility of non-Candida albicans species in Iran - Arian Alhani; Golsa Moshiri; Ensieh Lotfali (Novelty in Biomedicine)
Background: Candidiasis is among the most widespread infections caused by fungi species. Although C. albicans still serves as the primary source of this infection, the occurrence and antifungal resistance of non-Candida albicans species seem to be increasing.